MENISCAL TEARS - Dzoleva Tolevska, Roza; Popovska A; Georgieva, D; Samardziski, Milan; Bozinovski, Zoran; Nanceva, Jasminka; Georgiev, Antonio; Gjoshev S; Jovanovski-Srceva, M (Faculty for Physical Education, 2016)
Meniscus is the most commonly injured structure in the knee joint. Meniscal tear patterns incude vertical tears, oblique, complex and horizontal. Aim: The aim of this study is to present the distribution of different types of meniscal tears diagnosed and treated with arthroscopy. Material and methods: Between 2013 and 2015, at the University clinic for orthopaedic surgery, 137 patients with meniscal tears and averageage of26 t 15yearswerediagnosedandtreatedwitharthroscopy.Results:Out of137patients with meniscal tear, 109 (79.6%) patients had medial meniscal tear and 28 (20.4%) had lateral meniscal tear. Male female ratio was 3:1. Distribution of vertical, oblique, horizontal and complex medial meniscal tear was 16 (14.7%), 83 (76.1%), 6 (5.5%) and 4(3.7%6)respectively. Distribution of vertical (longitudinal and radial), oblique, horizontal and complex lateral meniscal tear was 5 (17.9%), 18 (64.3%), 2 (7.1%) and 3 (10.7%) respectively. Conclusion: Arthroscopy is essential for diagnosis and treatment of meniscal tears. In our study, medial meniscus is more frequently injured than lateral meniscus and horizontal meniscal tears appear less then oblique and vertical meniscal tears.
Keywords: meniscal tears; arthroscopy; knee